Micro:bit for mad scientists : 30 clever coding and electronics projects for kids - Monk, Simon (No Starch Press, 2019)
"A beginner-friendly collection of electronics projects for the Micro:bit. Teaches how to code in MicroPython and JavaScript Blocks, as well as how to build specific mad scientist themed projects such as a magnetic door alarm, a lie detector, and an irregular wall clock"--